2005
DOI: 10.1620/tjem.206.261
|View full text |Cite
|
Sign up to set email alerts
|

Successful Conservative Treatment of a Cesarean Scar Pregnancy with Uterine Artery Embolization

Abstract: Ectopic pregnancy developing in a previous Cesarean section scar is rare and is associated with catastrophic complications, such as uterine rupture and uncontrollable bleeding, which may lead to loss of the uterus. The operative treatments that have been reported for cesarean scar pregnancy are dilatation and curettage and excision of trophoblastic tissues using either laparotomy or laparoscopy. Recently, conservative treatment of scar pregnancy with locally and/or systemically administered methotrexate (MTX) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 13 publications
0
66
0
5
Order By: Relevance
“…In addition, we expected that the bleeding risk after secondary procedure, such as uterine curettage, would be reduced by embolization. The effi cacy of uterine artery embolization before the management of Cesarean scar pregnancy was already reported in previous studies [5,12]. Sugawara et al [5] reported a case of scar pregnancy treated with selective transarterial embolization in combination with subsequent dilatation and curettage and local or systemic injections of MTX.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, we expected that the bleeding risk after secondary procedure, such as uterine curettage, would be reduced by embolization. The effi cacy of uterine artery embolization before the management of Cesarean scar pregnancy was already reported in previous studies [5,12]. Sugawara et al [5] reported a case of scar pregnancy treated with selective transarterial embolization in combination with subsequent dilatation and curettage and local or systemic injections of MTX.…”
Section: Discussionmentioning
confidence: 76%
“…These conditions are challenging to diagnose and have higher risk of bleeding and uterine rupture [3,4]. Due to the severity of complications and possibility of hysterectomy, early diagnosis is critical [5]. However, there is still no standard treatment modality.…”
mentioning
confidence: 99%
“…Patients who have experienced different cesarean segments give off an impression of being at expanded hazard for in-scar implantation of the ensuing pregnancy on account of expanded scar surface zone [4,8,9]. With the coming of transvaginal sonography and with the utilization of saline imbuement, it is conceivable to survey postcaesarean area uterine divider respectability even in the nonpregnant state [4,[10][11][12]. Cesarean segment scar deformity is distinguished by the nearness of liquid inside the entry point site [12] or any filling imperfection, which is characterized as a triangular anechoic structure at the assumed site of the scar.…”
Section: Discussionmentioning
confidence: 99%
“…If the pregnant reported no clinical evidence of suffering, such us bleeding or abdominal pain, and the diagnosis is made at an early stage, we can consider a conservative management with systemic or local injection of methotrexate, potassium chloride, and hyperosmolar glucose [17,21,[27][28][29]. However, recent reports evidenced that the cases treated with local or systemic methotrexate, often required laparotomy due to massive hemorrhage [30]. Lee et al [31], in a retrospective review, enlisted nine women diagnosed with ectopic pregnancy on previous cesarean section scar; seven of them underwent laparoscopic treatment, thus, the gestational sac was removed by laparoscopy without converting to laparotomy, and the scar defect was repaired by intracorporeal sutures.…”
Section: Discussionmentioning
confidence: 99%